2019
DOI: 10.2478/s11756-019-00294-z
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-glucosidase activity of novel pyrazolobenzothiazine 5,5-dioxide derivatives for the treatment of diabetes mellitus. Invitro combined with molecular docking approach

Abstract: Diabetes mellitus is a metabolic disease caused due to the improper secretion of insulin which leads to hyperglycaemia. According to the International Diabetes Federation (IDF), 371 million people are affected by diabetes worldwide, while 7 million people are suffering from this disease in Pakistan. Pyrazolobenzothiazine 5,5-dioxide derivatives have anti-bacterial, anti-inflammatory, antioxidant activity and have the potential to treat diabetes and other diseases. This study was designed to perform in-silico a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…Similarly, various 1,2-benzothiazine 1,1-dioxides have been reported as antileukemic [25][26][27], 11β-HSD1 inhibitors [28], endotheline receptor antagonists [29], antimalarial agents [30], MAO inhibitors [31], antiallergic agents [32], antithrombotics [33], antiparasitic [34], antimicrobials [35,36], antioxidants [37], inhibitors of calpain I [38], and aldose reductase enzymes [39,40]. Our research group is involved in the search for novel and more effective antidiabetic agents [41][42][43][44][45], and in this context we have synthesized novel 1,2-benzothiazine-N-arylacetamides and screened them for their in silico and in vitro α-glucosidase inhibitory potential.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, various 1,2-benzothiazine 1,1-dioxides have been reported as antileukemic [25][26][27], 11β-HSD1 inhibitors [28], endotheline receptor antagonists [29], antimalarial agents [30], MAO inhibitors [31], antiallergic agents [32], antithrombotics [33], antiparasitic [34], antimicrobials [35,36], antioxidants [37], inhibitors of calpain I [38], and aldose reductase enzymes [39,40]. Our research group is involved in the search for novel and more effective antidiabetic agents [41][42][43][44][45], and in this context we have synthesized novel 1,2-benzothiazine-N-arylacetamides and screened them for their in silico and in vitro α-glucosidase inhibitory potential.…”
Section: Introductionmentioning
confidence: 93%
“…Our research group is involved in the search for novel and more effective antidiabetic agents [41][42][43][44][45], and in this context we have synthesized novel 1,2-benzothiazine-Narylacetamides and screened them for their in silico and in vitro α-glucosidase inhibitory potential.…”
Section: Synthetic Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…A hydrophobic contact between Trp376, Ile441, Trp516, Met519, Trp613, and Phe649 residues results in the stabilization. [32] Taj et al [33] have reported that pyrazolobenzothiazine 5,5-dioxide derivatives inhibit Asp203, Asp542, Asp327, His600, and Arg526 residues of human maltase-glucoamylase enzyme that is related to the human α-glycosidase.…”
Section: The 4-phenyl Moiety Also Formed Aromatic Hydrogen Bonds Withmentioning
confidence: 99%
“…During our contemplation on this paper, we get to know that combination of two structurally different but biologically and medicinally active scaffolds can lead to revolutionary hike in their potency when compare to their individual influence. For instance, combination of 1,2-benzothiazine with pharmaceutically active derivatives of quinolones, [64] piprazine, [36][37]54,56,62] azoyls, [65][66] and pyrazoles [58,72,75,[78][79][80][81]83,[88][89] lead to even more active compounds which makes the researchers job easier to invent superior drug candidate. Also, performance of 1,2benzothiazines increases when they exist in complex forms with metals like Copper (II), Zinc (II), Nickel (II), Cobalt (II) and Ruthenium (III), [50][51][52][53] with enhanced pharmacokinetics and reduces side effects.…”
Section: Introductionmentioning
confidence: 99%